2005
DOI: 10.1152/ajprenal.00301.2004
|View full text |Cite
|
Sign up to set email alerts
|

Basolateral K+conductance in principal cells of rat CCD

Abstract: Whole cell K ϩ current was measured by forming seals on the luminal membrane of principal cells in split-open rat cortical collecting ducts. The mean inward, Ba 2ϩ -sensitive conductance, with 40 mM extracellular K ϩ , was 76 Ϯ 12 and 141 Ϯ 22 nS/cell for animals on control and high-K ϩ diets, respectively. The apical contribution to this was estimated to be 3 and 16 nS/cell on control and high-K ϩ diets, respectively. To isolate the basolateral component of whole cell current, we blocked ROMK channels with ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 53 publications
3
30
0
Order By: Relevance
“…K loading increases the density of apical SK channels about fourfold while aldosterone alone does not (20). The basolateral K ϩ conductance is enhanced by about twofold with a high-K diet (11). No comparable measurements are available for the aldosterone-treated condition, but we assume a similar increase as both cases are associated with a significant amplication of basolateral membrane surface area (27,28,31).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…K loading increases the density of apical SK channels about fourfold while aldosterone alone does not (20). The basolateral K ϩ conductance is enhanced by about twofold with a high-K diet (11). No comparable measurements are available for the aldosterone-treated condition, but we assume a similar increase as both cases are associated with a significant amplication of basolateral membrane surface area (27,28,31).…”
mentioning
confidence: 89%
“…Maximal pump rates were set at 17 nA/mm, slightly higher than those measured under nonstimulated conditions (18), and K Na , the intracellular Na concentration required for half-maximal pump turnover, was assumed to be 10 mM. The basolateral K ϩ conductance under conditions of 5 mM peritubular K ϩ was taken to be 5,800 nS/mm (11). Paracellular conductance was assumed to be 300 nS/mm based on a resistance of 1 k⍀ ⅐cm 2 .…”
Section: Modeling Na and K Transport In The Rat Ccdmentioning
confidence: 99%
“…CCDs were microdissected as previously described (26,32), and principal cells were optically identified as flat and polygonal cells in contrast to the round and protuberant intercalated cells (5,26).…”
Section: Single-channel Analysismentioning
confidence: 99%
“…From whole cell clamp studies on mouse CCD cells (21), CCD-IRK3, a 15-pS inwardly rectifying K ϩ channel cloned from the M1 mouse collecting duct cell line, which presents a high degree of homology with human inwardly rectifying K ϩ (Kir) 2.3 channel (46), is thought to be the 18-pS channel described in rat CCD principal cells (45). Using whole cell patch-clamp technique and noise analysis of K ϩ current measurements of rat CCD principal cells, Gray et al (5) indicated that the native ϳ30-pS K ϩ channel (45) shared some properties of members of the Kir4/Kir5 subfamily of channels. However, no comparison of the properties at the single-channel level of native K ϩ channels in the basolateral membrane of CCD principal cells with those of cloned channels has been conducted.…”
mentioning
confidence: 99%
“…Thus it is possible that the 18-pS K channel is a major type of K channel in the basolateral membrane of principal cell in the CCD from the rat kidney. The notion that 18-pS K channels may be major contributors to basolateral K conductance has also been shown with whole cell patch experiments in which noise analysis reveals that 18-pS K channels may account for 65% of whole cell K current (6). Thus inhibition of 18-pS K channels by AA is expected to have an effect on the basolateral membrane potential.…”
Section: Discussionmentioning
confidence: 72%